Reimagining Education: Teaching and Learning in a Global Community - Lotta Larson (Educational Considerations, 2019)
We can no longer debate if global awareness is essential. It is time to reimagine education and carefully consider how to prepare students and educators to thrive in a malleable world.
Keywords: education